(فرہنگِ اصطلاحات ، فرہنگ برائے تکنیکی اصطلاحاتِ تاریخ اور سیاسیات (انگریزی اردو - (:unkn) unknown (Bureau for Promotion of Urdu language, Department of Education, Government of India, 1990)
This is an English-Urdu glossary consisting of terminologies especially used in the disciplines of History and Political Science.
Glossary of Technical Terms : History and Political Science (English-Urdu)
Keywords: Glossary; Urdu; Urdu; English